Historical-conceptual elements of Western educational systems. The Costa Rican case within a globalization framework - Rodríguez Varela, Francisco José (2019)
Thinking of education requires an exercise of epistemological surveillance thatallows visualizing the complex gear existing among the historical processes ofhuman evolution, where organizational models are brought about to seek thedevelopment or wellbeing of individuals, besides increasingly evident trendsin which knowledge is subordinated to institutionalism. In this regard, it isimportant to review some general features of education that are typical of thewestern world –with an emphasis on the Costa Rican scenario- and that allowestablishing a dialogue between stages such as colonization and modernity –for example-, and the creation of educational models that replicate the modusoperandi of the economic system, leading to a landscape that does not matchthe principles of a search for overall wellbeing and respect for the diversity ofhuman thought under a framework of the ethical and philosophical structure ofeducation as a fundamental right of every human being.